Studies on Viburnum nervosum Hook: Chemistry and Spectroscopy of Bergenin and its Derivatives (The East and Central African Journal of Pharmaceutical Sciences, 2018)
This paper reports on the isolation of bergenin from Viburnum nervosum (Capprifoliaceae). This is the first time the compound has been isolated from the genus Viburnum. Derivatives of bergenin namely bergenin diethyl ether, bergenin pentaacetate and bergenin diethyl ether triacetate were prepared and characterized using spectroscopic data.
Keywords: Bergenin; bergenin derivatives; Viburnum nervosum